State Immunity and Cultural Objects on Loan. - Woudenberg, Nout van (BRILL, 2012)
This study examines whether there is any rule of (customary) international law stipulating that cultural objects belonging to foreign States that are on loan for temporary exhibition are immune from seizure, or whether such a rule is emerging.